Laplace’s Law Dictates the Timing of Birth, the Duration of Pregnancy, and the Mode of Delivery Through Exponential Uterine Wall Tension and Hormonal Milieu, as Well as Their Light- Dark Cycle Modulation: A Hypothesis - FRCOG, Ali Hegazy (Archives of Clinical and Medical Case Reports, 2025)
Background: The laws of physics govern the functions of human body organs. However, the law of physics that controls uterine function during pregnancy remains unknown. Spontaneous preterm labor, labor dystocia, and post-term pregnancy are significant obstetric complications, and their biological mechanisms are poorly understood. A failure to understand uterine function during pregnancy is a major shortcoming in modern healthcare. Objective: Supporting the hypothesis, Laplace's Law dictates the timing of birth, the duration of pregnancy, and the mode of delivery through exponential uterine wall tension and hormonal milieu, as well as their light-dark cycle modulation. We will refer to this hypothesis as Hegazy's Hypothesis for Gestation (HHG). Method: A literature search was conducted using Medical Subject Headings terms on every topic of the hypothesis in PubMed, in addition to manually searching for additional references. The scripts that were found were reviewed, examined, and condensed, along with two 40-second 3D animations. Results: The anatomical existence of the isthmus of the cervix should be reconsidered, as there has been no convincing evidence to support its existence since Aschoff first proposed it in 1905. Uterine mechanotransduction may be the primary mechanism and system that controls uterine function during pregnancy through exponential uterine wall tension (EUWT) and the hormonal milieu. EUWT has anatomical and functional components, determinants, modulators, and a physiological mechanotransduction effect. EUWT is created and maintained by the complex interaction between the gestational sac, uterus, and cervix, whose primary function is the maintenance of EUWT. EUWT mechanotransduction with progesterone/estrogen modulation induces the stretch-dependent inhibitory uterine system (SDIUS). The SDIUS is the primary system that maintains pregnancy through autonomic intrinsic myometrial cell characteristics (AIMCC). AIMCC enables the uterus to control its function autonomously and intrinsically, due to the Myometrial Tension-Contraction Interaction (MTCI) characteristic, where high tension induces relaxation and low tension induces contraction. EUWT mechanotransduction with progesterone/estrogen modulation also induces the stimulatory system by inducing myometrial hyperplasia and hypertrophy. Embryologically and evolutionarily, the uterus is composed of two uteri. Uterine contractions (stimulatory system) create direct and indirect uterine-cervical interactions (DIDUCI). DIDUCI transforms the cervix into the lower uterine segment (LUS), through the TYVU pattern formation. Light-dark cycle modulation of the interactive inhibitory and stimulatory systems divides gestation into five clinical phases: growth, maturation, transition, parturition, and involution. Maturation phase (32-40 weeks): Nocturnally, oxytocin and melatonin modulate the stimulatory system. Additionally, cortisol modulates the inhibitory system, causing a transient nocturnal pause. The nocturnal synchronization and synergy of the two systems make the uterus an active organ at night, transforming the cervix into the LUS. This ultimately leads to nocturnal EUWT and SDUIS failure, dictating both pregnancy intervals and circadian timers. The successful transformation of the cervix into the LUS during late pregnancy is the cornerstone of pregnancy termination and achieving successful labor. The failure of this mechanism alone causes post-term pregnancy; if combined with the failure of the inhibitory system, it results in labor dystocia. A malfunction in the inhibitory system causes preterm labor. Conclusions: Pregnancy is in a state of balance between the opposing and interactive inhibitory and stimulatory systems, secondary to EUWT mechano-transduction and progesterone/estrogen modulation. The autonomous creation, maintenance, and eventual termination of EUWT, secondary to light-dark cycle modulation, make gestation an autonomic cycle with constant intervals and circadian timers, where EUWT malfunctions alter birth timing, pregnancy duration, and mode of delivery. Laplace's law measures EUWT which may be the law of physics that govern uterine function during pregnancy.